2007
DOI: 10.1016/j.molcel.2007.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Trm9-Catalyzed tRNA Modifications Link Translation to the DNA Damage Response

Abstract: Transcriptional and posttranslational signals are known mechanisms that promote efficient responses to DNA damage. We have identified Saccharomyces cerevisiae tRNA methyltransferase 9 (Trm9) as an enzyme that prevents cell death via translational enhancement of DNA damage response proteins. Trm9 methylates the uridine wobble base of tRNAARG(UCU) and tRNAGLU(UUC). We used computational and molecular approaches to predict that Trm9 enhances the translation of some transcripts overrepresented with specific argini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
410
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(431 citation statements)
references
References 36 publications
21
410
0
Order By: Relevance
“…The specificity of the observed phenotypes both in fission yeast and in worm is in favor of the second possibility and is reminiscent of the specific phenotype (cell cycle arrest) resulting from the absence of wobble inosine in fission yeast (40). This is also supported by a very recent study showing that deletion of the Trm9 tRNA ARG and tRNA GLU methyltransferase affects the translation of transcripts overrepresented with specific arginine and glutamate codons while the translation of average transcripts that contain a normal codon usage pattern is unaffected (41).…”
Section: Discussionmentioning
confidence: 70%
“…The specificity of the observed phenotypes both in fission yeast and in worm is in favor of the second possibility and is reminiscent of the specific phenotype (cell cycle arrest) resulting from the absence of wobble inosine in fission yeast (40). This is also supported by a very recent study showing that deletion of the Trm9 tRNA ARG and tRNA GLU methyltransferase affects the translation of transcripts overrepresented with specific arginine and glutamate codons while the translation of average transcripts that contain a normal codon usage pattern is unaffected (41).…”
Section: Discussionmentioning
confidence: 70%
“…Similar to other modifications, it is not clear whether transcription efficiency or fidelity or both are affected when the codon AAA has to be decoded by unmodified tRNA UUU Lys ; although Begley et al (35) described that S. cerevisiae Trm9-mediated tRNA modifications participate in the DNA damage response by enhancing translation elongation of general and specific stress proteins, they also reported later that those tRNA modifications lead to translation infidelity of specific transcripts, misfolding of the resulting proteins, and activation of the unfolded protein response pathway (36). Similarly, it has recently been suggested that Elongator mutants in budding yeast display basal proteostasis defects due to inefficient or incorrect translation, and this basal phenotype may be exacerbated in the presence of stress conditions (37).…”
Section: Discussionmentioning
confidence: 99%
“…2,[49][50][51] Moreover, DNA damage and replication failure can stimulate the activation of yeast cell death programs; 52 oxygen metabolism and ROS generation are thereby major causes of DNA damages. In yeast, several players involved in DNA-damage-regulated apoptosis have been found, including tRNA methyltransferase-9, which acts as a tRNA modifier that positively regulates the expression levels of major DNA-damage-response proteins, 53 or the peroxiredoxin Tsa1p, identified as a key peroxidase able to suppress genome instability. 54 Genomic instability, which contributes to aging in all eukaryotes, is intimately related to replication stress, which in yeast affects both chronological and replicative aging.…”
Section: Triggering Yeast Apoptosismentioning
confidence: 99%